2006
DOI: 10.1242/jcs.02826
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling: complexity at the surface

Abstract: Wnts are secreted proteins that are essential for a wide array of developmental and physiological processes. They signal across the plasma membrane by interacting with serpentine receptors of the Frizzled (Fz) family and members of the low-density-lipoprotein-related protein (LRP) family. Activation of Fz-LRP promotes the stability and nuclear localization of β-catenin by compromising the ability of a multiprotein complex containing axin, adenomatosis polyposis coli (APC) and glycogen synthase kinase 3 (GSK3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
377
0
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(391 citation statements)
references
References 126 publications
7
377
0
7
Order By: Relevance
“…This result supports the idea of two distinct receptor events, mediated by Lrp5/6 and Fz, respectively, which converge on b-catenin (Cadigan and Liu, 2006;Li et al, 2002).…”
Section: Wnt Activation By Dkk2supporting
confidence: 88%
See 2 more Smart Citations
“…This result supports the idea of two distinct receptor events, mediated by Lrp5/6 and Fz, respectively, which converge on b-catenin (Cadigan and Liu, 2006;Li et al, 2002).…”
Section: Wnt Activation By Dkk2supporting
confidence: 88%
“…Wnt/b-catenin pathway (Cadigan and Liu, 2006), (2) the planar cell polarity pathway (PCP), which does not involve b-catenin but recruits small GTPases of the rho/ cdc42 family to activate Jun kinase (JNK) and which at least in vertebrates appears to be triggered by Wnts (Tada et al, 2002) and (3) the Wnt/Ca 2 þ cascade, which is still controversial and may be partly overlapping with the PCP pathway (Kohn and Moon, 2005 (Semenov et al, 2001). This is because Dkks bind and modulate Wnt coreceptors of the lipoprotein receptor-related protein 5/6 class, which are indispensable for routing the Wnt signal to the b-catenin pathway .…”
Section: Dickkopf Review C Niehrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon binding β-catenin converts TCFs into transcriptional activators inducing target genes for proliferation and invasion [4,5]. However, Wnts can also bind FZDs independently of LRP, activate or inhibit canonical Wnt signalling depending on the receptor context and induce non-canonical signal transduction pathways involving Ca 2+ as a second messenger [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…These studies indicate that GSK3b might control the progression of EC by modifying the activation of NF-jB in different stages of tumorigenesis. Numerous studies reported that phospho-inactivation of GSK3b results in the degradation of c-Myc and b-catenin (Cadigan and Liu 2006;Yada et al 2004). b-Catenin is a critical component of adherent junction in stratified squamous epithelium of esophageal.…”
Section: Gsk3b Affects Tumorigenesis Of Ec Through Transcription Factmentioning
confidence: 99%